2008
DOI: 10.1128/aem.02459-07
|View full text |Cite
|
Sign up to set email alerts
|

Leaf Age as a Risk Factor in Contamination of Lettuce withEscherichia coliO157:H7 andSalmonella enterica

Abstract: Outbreaks of Escherichia coli O157:H7 infections have been linked increasingly to leafy greens, particularly to lettuce. We present here the first evidence that this enteric pathogen can multiply on the leaves of romaine lettuce plants. The increases in population size of E. coli O157:H7 in the phyllosphere of young lettuce plants ranged from 16-to 100-fold under conditions of warm temperature and the presence of free water on the leaves and varied significantly with leaf age. The population size was consisten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
114
4
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(124 citation statements)
references
References 42 publications
4
114
4
2
Order By: Relevance
“…In comparison with other studies on the survival of these pathogens on fresh produce (e.g., Aruscavage et al, 2008;Brandl and Amundson, 2008;Erickson et al, 2010a), we used growing butterhead lettuce plants cultivated under realistic northern European lettuce production conditions. The experiments were performed under the controlled conditions of a growth chamber, but in parallel an experiment in the greenhouse was made to evaluate whether the investigated factors are also important under conditions of current practice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In comparison with other studies on the survival of these pathogens on fresh produce (e.g., Aruscavage et al, 2008;Brandl and Amundson, 2008;Erickson et al, 2010a), we used growing butterhead lettuce plants cultivated under realistic northern European lettuce production conditions. The experiments were performed under the controlled conditions of a growth chamber, but in parallel an experiment in the greenhouse was made to evaluate whether the investigated factors are also important under conditions of current practice.…”
Section: Discussionmentioning
confidence: 99%
“…For each combination of pathogen and crop stage, a total of 14 plants were inoculated. Young plants were inoculated by immersion as described by Brandl and Amundson (2008). Nearly mature plants were spray-inoculated as immersion was not feasible for biosafety reasons.…”
Section: Plant Inoculations and Irrigationmentioning
confidence: 99%
See 1 more Smart Citation
“…Lettuce variety, maturity and seasonal effects throughout the time period of the experiments (November-April) may have influenced the plant physiology of the Iceberg lettuce leaves and thus the internalization of the pathogen's cells. Indeed, young lettuce leaves produce more nutrients (Brandl and Amundson, 2008), but we tried to minimize this effect by selecting Iceberg heads with uniform maturity stage based on the chart of maturity stages of Iceberg lettuce and selecting leaves with the same developmental stage for sample preparation. Furthermore, as the lettuce was store bought it could not be guaranteed that all the heads belonged to the same variety, it has already been shown that enteric pathogens may interact differently with different lettuce cultivars (Klerks et al, 2007;Quilliam et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Potential routes by which S. enterica and enterovirulent E. coli colonize edible plant parts in the field and under greenhouse conditions have been investigated (Fletcher et al, 2013;Islam et al, 2004;Moyne et al, 2011;Park et al, 2012). Pre-harvest, microbiological quality of fresh produce is affected by the presence of native epiphytic microbiota (including phytopathogens), the types and levels of irrigation, and the use of soil amendments (Allard et al, 2014;Brandl, 2006Brandl, , 2008Brandl and Amundson, 2008;Franz and van Bruggen, 2008;Gu et al, 2013;GutierrezRodriguez et al, 2012;Moyne et al, 2011;Park et al, 2012;PozaCarrion et al, 2013). However, relatively little remains known about the impact of crop production practices on post-harvest susceptibility of raw fruits and vegetables to human pathogens.…”
Section: Introductionmentioning
confidence: 99%